2020
DOI: 10.1016/j.polymer.2020.123003
|View full text |Cite
|
Sign up to set email alerts
|

Bio-based polyether from limonene oxide catalytic ROP as green polymeric plasticizer for PLA

Abstract: In this work, the polymerization of Limonene Oxide (LO) has been achieved using an Earth abundant metal-based catalyst developed in our group, that is very active in ring opening polymerization (ROP) processes. The bio-based polylimonene ether (PLO) obtained had low molecular weight and good thermal properties, thus being a potential green polymeric additive for other bio-based polymers such as PLA. Hence, we have explored its ability to influence PLA properties. The addition of only 10 wt %, led to the modifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 44 publications
3
24
0
1
Order By: Relevance
“…A significant decrease in the thermal stability (initial decomposition temperature T 5 %) of PLA films was observed with the addition of the ATBC plasticiser. Similar results were observed by Maiza et al [ 3 ] and Sessini et al [ 35 ]. Nelson et al [ 46 ] reported that a higher degree of crystallinity is directly involved in the higher thermal stability of L-CNCs.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A significant decrease in the thermal stability (initial decomposition temperature T 5 %) of PLA films was observed with the addition of the ATBC plasticiser. Similar results were observed by Maiza et al [ 3 ] and Sessini et al [ 35 ]. Nelson et al [ 46 ] reported that a higher degree of crystallinity is directly involved in the higher thermal stability of L-CNCs.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, the C–O stretching bands of CH–O at 1180 cm −1 and O–C=O groups at 1127 cm −1 , 1080 cm −1 and 1043 cm −1 , respectively, were observed. The same absorption band characteristic was detected by Sessini et al [ 35 ], Lee et al [ 36 ], Weng et al [ 37 ] and Amorin et al [ 38 ]. Moreover, bending frequencies for CH 3 have bends identified at 1452 cm −1 , 1382 cm −1 and 1359 cm −1 , as well as bends related to the C=O double-bound around 700 cm −1 [ 39 ].…”
Section: Resultssupporting
confidence: 81%
“…Furthermore, green composite materials can strongly contribute to the development of the so-called Circular Bioeconomy as these are obtained from natural resources or, more sustainably, wastes and can be fully biodisintegrated under different composting conditions [5]. In the area of biodegradable polymers, polylactide (PLA) has made a large contribution since this biopolyester is both fully bio-based, obtained from starch-rich materials, and compostable in controlled industrial facilities [6,7]. PLA is a linear thermoplastic that shows high mechanical resistance and thermal stability, good transparency, and water-barrier performance, by which it can potentially substitute some polymer commodities, such as polypropylene (PP) or polystyrene (PS), in several applications, ranging from food packaging [8][9][10] to automotive [11], biomedicine [12], or electronics [13].…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Park described the photoinitiated cationic ring-opening polymerizations with diaryliodonium salts or triarylsufonium salts as photoinitiators with very poor control of the polymerization-the polymers generated had very low molecular weights and high disperties [130]. The only other example has been reported by us using a very active aluminum catalyst for ROP, [AlMeCl(OR)] (OR = 2,6-(CHPh 2 ) 2 -4-t Bu-C 6 H 2 O) (Scheme 8) [131,132]. This catalyst is able to efficiently polymerize (+)-limonene oxide in just 30 min, with a preference for cis-isomer polymerization.…”
Section: Polymerization Of Terpenoidsmentioning
confidence: 99%